1984
DOI: 10.2527/jas1984.5911
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dam Age, Prepartum Nutrition and Duration of Labor on Productivity and Postpartum Reproduction in Beef Females

Abstract: Sixty-two, 2-yr-old heifers and 65 cows, 4 to 7 yr old, were assigned randomly at 60 d before the median predicted calving date to a factorially designed study. Main effects were: age of dam (heifer or cow), moderate (M) or high (H) precalving feed level (110 or 135% of National Research Council recommendation) and short (S) or prolonged (P) duration of Stage II of parturition. After calving, all dams were placed in the same range pastures and received supplemental hay and a grain-salt mix until adequate range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
2
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 11 publications
4
26
2
1
Order By: Relevance
“…Similar birth weights of calves in the present study are consistent with Long et al (2010b) and others (Doornbos et al, 1984;Goehring et al, 1989;Houghton et al, 1990) who showed that restriction of dietary energy before the last trimester of gestation did not influence birth weight or gestational length. Additionally, it has been reported that if postnatal nutrition is adequate, any effects of maternal diets during mid or late gestation on birth weights will not result in altered calf BW either before or at weaning (Hight, 1968;Freetly et al, 2000).…”
Section: Discussionsupporting
confidence: 95%
“…Similar birth weights of calves in the present study are consistent with Long et al (2010b) and others (Doornbos et al, 1984;Goehring et al, 1989;Houghton et al, 1990) who showed that restriction of dietary energy before the last trimester of gestation did not influence birth weight or gestational length. Additionally, it has been reported that if postnatal nutrition is adequate, any effects of maternal diets during mid or late gestation on birth weights will not result in altered calf BW either before or at weaning (Hight, 1968;Freetly et al, 2000).…”
Section: Discussionsupporting
confidence: 95%
“…It appears that greater cow BW and BCS at calving led to increased calf preweaning BW gain. This is in contrast to previous reports that milk production or preweaning and 205-d adjusted weaning BW of calves are not influenced by cow body energy reserves, as indicated by BCS, when cows are in moderate body condition at the time of parturition (Doornbos et al, 1984;DeRouen et al, 1994;Spitzer et al, 1995;Ciccioli et al, 2003).…”
Section: Postpartum Cow Bw and Bcscontrasting
confidence: 99%
“…That is, when variables other than those reported in Table 3 were included in the specification the estimated coefficients on those variables were not significantly different from zero, the estimated coefficients in Table 3 Doornbos et al (1984).…”
Section: Resultsmentioning
confidence: 99%
“…With OLS analysis and a broader categorization (age of dam X obstetrical assistance) an effect on PPI was not statistically discernible (Doornbos et al 1984 …”
Section: Resultsmentioning
confidence: 99%